No evidence for schistosome parasite fitness trade-offs in the intermediate and definitive host - Winka Le Clec’h; Frédéric D. Chevalier; Kathrin Jutzeler; Timothy J. C. Anderson (Parasites & Vectors, 2023)
Abstract Background The trematode parasite Schistosoma mansoni uses an aquatic snail intermediate and a vertebrate definitive host to complete its life cycle. We previously showed that a key transmission trait—the number of cercariae larvae shed from infected Biomphalaria spp. snails—varies significantly within and between different parasite populations and is genetically controlled by five loci. We investigated the hypothesis that the success of parasite genotypes showing high propagative fitness in the intermediate snail host may be offset by lower reproductive fitness in the definitive vertebrate host. Methods We investigated this trade-off hypothesis by selecting parasite progeny producing high or low number of larvae in the snail and then comparing fitness parameters and virulence in the rodent host. We infected inbred BALB/c mice using two Schistosoma mansoni parasite lines [high shedder (HS) and low shedder (LS) lines] isolated from F2 progeny generated by genetic crosses between SmLE (HS parent) and SmBRE (LS parent) parasites. We used the F3 progeny to infect two populations of inbred Biomphalaria glabrata snails. We then compared life history traits and virulence of these two selected parasite lines in the rodent host to understand pleiotropic effects of genes determining cercarial shedding in parasites infecting the definitive host. Results HS parasites shed high numbers of cercariae, which had a detrimental impact on snail physiology (measured by laccase-like activity and hemoglobin rate), regardless of the snail genetic background. In contrast, selected LS parasites shed fewer cercariae and had a lower impact on snail physiology. Similarly, HS worms have a higher reproductive fitness and produced more viable F3 miracidia larvae than LS parasites. This increase in transmission is correlated with an increase in virulence toward the rodent host, characterized by stronger hepato-splenomegaly and hepatic fibrosis. Conclusions These experiments revealed that schistosome parasite propagative and reproductive fitness was positively correlated in intermediate and definitive host (positive pleiotropy). Therefore, we rejected our trade-off hypothesis. We also showed that our selected schistosome lines exhibited low and high shedding phenotype regardless of the intermediate snail host genetic background. ​ Graphical Abstract